Tyrosine phosphorylation profiling in FGF-2 stimulated human embryonic stem cells. - Vanessa M Y Ding (Public Library of Science (PLoS), 2011)
The role of fibroblast growth factor-2 (FGF-2) in maintaining undifferentiated human embryonic stem cells (hESC) was investigated using a targeted phosphoproteomics approach to specifically profile tyrosine phosphorylation events following FGF-2 stimulation. A cumulative total number of 735 unique tyrosine phosphorylation sites on 430 proteins were identified, by far the largest inventory to date for hESC. Early signaling events in FGF-2 stimulated hESC were quantitatively monitored using stable isotope dimethyl labeling, resulting in temporal tyrosine phosphorylation profiles of 316 unique phosphotyrosine peptides originating from 188 proteins. Apart from the rapid activation of all four FGF receptors, trans-activation of several other receptor tyrosine kinases (RTKs) was observed as well as induced tyrosine phosphorylation of downstream proteins such as PI3-K, MAPK and several Src family members. Both PI3-K and MAPK have been linked to hESC maintenance through FGF-2 mediated signaling. The observed activation of the Src kinase family members by FGF-2 and loss of pluripotent marker expression post Src kinase inhibition may point to the regulation of cytoskeletal and actin depending processes to maintain undifferentiated hESC.